The Influence of Training Programs on The Performance of Hajj and Umrah Marketers at Panin Dubai Sharia Bank - Azizah, Farah Nur; Firdayetti, Firdayetti (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
Marketing performance that is able to provide the best quality and service to each customer is expected to further increase public trust and interest in using the products and services offered. The aim of the following research is to find out and expand insight into the influence of training programs on the marketing performance of Hajj and Umrah at Bank Panin Dubai Syariah. This type of research was designed based on quantitative methods using non-parametric testing, namely the Wilcoxon Test. Because it is quantitative, this research data is secondary using Relation Officer Academy (ROSA) data. The data analysis technique is the SPSS version 25 program. The testing stages are the normality test via Shapiro-Wilk, the average difference test via the Wilxocon test because the data used is not normal. The results of data analysis show that providing training programs can have a positive influence in improving marketing performance at Bank Panin Dubai Syariah. Based on the Wilcoxon test, the average achievement value of 18 samples is included in the Positive Rating, that is, all samples tested have a Post Test value that is greater than the Pre-Test value, meaning that all marketing performance achievements have increased before and after being given training